Prasugrel versus clopidogrel in stent-assisted coil embolization of unruptured intracranial aneurysms. Issue 1 (February 2017) - Sedat, Jacques; Chau, Yves; Gaudart, Jean; Sachet, Marina; Beuil, Stephanie; Lonjon, Michel
Background: Thromboembolic complications are the main problem in stent-assisted coil embolization of unruptured intracranial aneurysms. The combination of aspirin and clopidogrel is generally used to decrease these complications, but some patients do not respond to clopidogrel and have a higher risk of stent thrombosis. In cardiology, clinical trials have shown that prasugrel reduced the incidence of ischaemic events in patients with acute coronary syndrome compared with clopidogrel but, according to several authors, prasugrel would produce an increased risk of cerebral haemorrhagic complications. Objective: The purpose of this study was to determine whether prasugrel would be more effective than clopidogrel in reducing procedural events in patients with an unruptured aneurysm treated endovascularly with coils and stent. Materials and methods: Two hundred consecutive patients with intracranial aneurysms were treated using coiling and stenting procedures. The first 100 patients were administered a dual antiplatelet of aspirin and clopidogrel, while the remaining 100 patients were administered a dual antiplatelet of aspirin and prasugrel. In each group data were collected on procedural and periprocedural haemorrhagic and ischaemic complications. Results: Aneurysmal occlusion and haemorrhagic complications rates were identical in both groups. The number of thromboembolic events observed in the two groups of our study did not differ significantly, but the prasugrel group included more wide-neck aneurysms and more flow-diverted stents. Moreover, complications in the prasugrel group were more benign, explaining the significant difference in clinical outcomes between the two groups on Day 30. Conclusions: Prasugrel reduces the clinical consequences of thromboembolic complications of endovascular treatment with stenting and coiling of unruptured intracranial aneurysms.